Stochastic and Age‐Dependent Proteostasis Decline Underlies Heterogeneity in Heat‐Shock Response Dynamics. Issue 30 (1st July 2021) - Vertti‐Quintero, Nadia; Berger, Simon; Casadevall i Solvas, Xavier; Statzer, Cyril; Annis, Jillian; Ruppen, Peter; Stavrakis, Stavros; Ewald, Collin Y.; Gunawan, Rudiyanto; deMello, Andrew J.
Abstract: Significant non‐genetic stochastic factors affect aging, causing lifespan differences among individuals, even those sharing the same genetic and environmental background. In Caenorhabditis elegans, differences in heat‐shock response (HSR) are predictive of lifespan. However, factors contributing to the heterogeneity of HSR are still not fully elucidated. Here, the authors characterized HSR dynamics in isogenic C. elegans expressing GFP reporter for hsp‐16.2 for identifying the key contributors of HSR heterogeneity. Specifically, microfluidic devices that enable cross‐sectional and longitudinal measurements of HSR dynamics in C. elegans at different scales are developed: in populations, within individuals, and in embryos. The authors adapted a mathematical model of HSR to single C. elegans and identified model parameters associated with proteostasis—maintenance of protein homeostasis—more specifically, protein turnover, as the major drivers of heterogeneity in HSR dynamics. It is verified that individuals with enhanced proteostasis fidelity in early adulthood live longer. The model‐based comparative analysis of protein turnover in day‐1 and day‐2 adult C. elegans revealed a stochastic‐onset of age‐related proteostasis decline that increases the heterogeneity of HSR capacity. Finally, the analysis of C. elegans embryos showed higher HSR and proteostasis capacity than young adults and established transgenerational contribution to HSR heterogeneity that depends on maternal age. Abstract : The causes of individual‐to‐individual heterogeneity of Heat‐shock Response (HSR) are investigated. Microfluidic‐based experiments and mathematical modeling are used to characterize HSR dynamics and identify key regulators of HSR variability in  Caenorhabditis elegans . It is found that the stochastic onset of proteostasis collapse in somatic tissues during early adulthood reflects individual protein translation capacity, predicting heterogeneous aging in isogenic  C. elegans .